N10‐carbonyl‐substituted phenothiazines inhibiting lipid peroxidation and associated nitric oxide consumption powerfully protect brain tissue against oxidative stress. (12th June 2019) - Keynes, Robert G.; Karchevskaya, Anastasia; Riddall, Dieter; Griffiths, Charmaine H.; Bellamy, Tomas C.; Chan, A. W. Edith; Selwood, David L.; Garthwaite, John
Abstract: During some investigations into the mechanism of nitric oxide consumption by brain preparations, several potent inhibitors of this process were identified. Subsequent tests revealed the compounds act by inhibiting lipid peroxidation, a trigger for a form of regulated cell death known as ferroptosis. A quantitative structure–activity study together with XED (eXtended Electron Distributions) field analysis allowed a qualitative understanding of the structure–activity relationships. A representative compound N‐(3, 5‐dimethyl‐4H‐1, 2, 4‐triazol‐4‐yl)‐10H‐phenothiazine‐10‐carboxamide (DT‐PTZ‐C) was able to inhibit completely oxidative damage brought about by two different procedures in organotypic hippocampal slice cultures, displaying a 30‐ to 100‐fold higher potency than the standard vitamin E analogue, Trolox or edaravone. The compounds are novel, small, drug‐like molecules of potential therapeutic use in neurodegenerative disorders and other conditions associated with oxidative stress. Abstract : N 10 ‐carbonyl‐substituted phenothiazines exemplified by DT‐PTZ‐C inhibit lipid peroxidation and oxidative stress, which are key drivers of ferroptosis, a form of regulated cell death.